Ensino de Filosofia na Educação Básica: a Tertúlia Filosófica como possibilidade de formação para a autonomia e resistência em Adorno - Souza, Rogean Rodrigues (2020)
The present research work reflects on the challenges of philosophical training in today's high school in the face of social conditions which directly interfere in the formation of the subject. The ideas of the philosopher Theodor Adorno has shown how educational process has docilely bowed to capitalist interests and, thus, it has denied authentic formation to the youth at this learning stage. Enlightenment (Aufklärung) as an unfolding of rationality in history, despite its porposal, did not fulfill its promise to make man free from the tutelage of others. It launched humanity into another form of minority: the technological servitude that converted reason into yet another instrument in favor of barbarism. The great catastrophes experienced in the last century, as the two great world wars, the horrors of the Nazi concentration camps, just to name a few, attest to the semi-formation to which society is subjected. It is evident, therefore, that the development of capitalism with all the technological paraphernalia affected all dimensions of the subject's life, including his education. And school as a training institution has shown itself to be unable to provide emancipatory training, thus, it has offered a semi-training that is deepened by the influence of the products of the cultural industry. In this scenario, cultural formation (bildung) is negatively affected and becomes semiculture (halbildung). The Brazilian context with the recent reforms attests to this situation. It is necessary to consider that any methodological proposal to think about education, in Adorno, implies resorting to new formative experiences in which it is possible to rethink the social structure and which can at the same time effect the imperative to avoid barbarism. In this intention, a methodological proposal is offered, Tertúlia Filosófica, as a pedagogical subsidy for the discipline in this teaching stage. Thus, the question is answered about the possibility of still developing training for autonomy in times of global capitalism, through philosophy. The goal is, therefore, to offer research that envisions the possibility, albeit small, of philosophical training in the context of basic education.